Pengaruh Gaya Kepemimpinan Dan Disiplin Kerja Terhadap Kinerja Karyawan Pada Pt. Smec Denka Indonesia - Dwi Astuti; Lily Setyawati Kristianti; Irfan Rizka Akbar (Journal of Research and Publication Innovation, 2023)
This study aims to examine the Effect of Leadership Style and Work Discipline on Employee Performance Partially and Simultaneously at PT. SMEC Denka Indonesia, this research method uses a quantitative analysis method, which uses 52 respondents. The sampling method used in this research is saturated sampling. The data analysis processing technique uses descriptive analysis, classical assumption test, regression test, correlation test, coefficient of determination test, and hypothesis testing. The data was processed by SPSS version 26. Hypothesis test showed that Leadership Style had no partial effect on employee performance as indicated by tcount -1.786 < ttable 1.66940. Thus H1 is rejected. Meanwhile, Work Discipline has a partial effect on employee performance, which is indicated by tcount 7.761 > ttable 1.66940. Thus H2 is accepted. Simultaneous hypothesis testing shows that Leadership Style and Work Discipline have an effect on Employee Performance with the regression equation y = 6.662 + (-0.156)x1 + 0.968x2. The correlation coefficient value is 0.746, which means that the independent variable and the dependent variable have a very strong relationship with the coefficient of determination or simultaneous influence of 55.6% while the remaining 44.4% is influenced by other factors. the results of the f statistic test have a probability of 0.000 < 0.05 or the value of fcount 30,672 > ftable 2.75. Thus H3 is accepted.